Early detection of neutralizing antibodies against SARS-CoV-2 in COVID-19 patients in Thailand. - Opass Putcharoen; Supaporn Wacharapluesadee; Wan Ni Chia; Leilani Paitoonpong; Chee Wah Tan; Gompol Suwanpimolkul; Watsamon Jantarabenjakul; Chanida Ruchisrisarod; Phanni Wanthong; Jiratchaya Sophonphan; Pajaree Chariyavilaskul; Lin-Fa Wang; et al. (PLoS ONE, 2021)
Background The presence of neutralizing antibodies (NAbs) is an indicator of protective immunity for most viral infections. A newly developed surrogate viral neutralization assay (sVNT) offers the ability to detect total receptor binding domain-targeting NAbs in an isotype-independent manner, increasing the test sensitivity. Thus, specimens with low IgM/ IgG antibody levels showed strong neutralization activity in sVNT. Methods This study aimed to measure the %inhibition of NAbs measured by sVNT in PCR-confirmed COVID-19 patients. The sensitivity of sVNT for the diagnosis of SARS-CoV-2 infection and its kinetics were determined. Results Ninety-seven patients with PCR-confirmed SARS-CoV-2 infection were included in this study. Majority of the patients were 21-40 years old (67%) and 63% had mild symptoms. The sensitivity of sVNT for the diagnosis of SARS-CoV-2 infection was 99% (95% confidence interval (CI) 94.4-100%) and the specificity was 100% (95% CI 98.3-100%). The negative predictive value of sVNT from the samples collected before and after 7 days of symptom onset was 99.5% (95% CI 97.4-100%) and 100% (95% CI 93.8-100%), respectively. The level of inhibition at days 8-14 were significantly higher than days 0-7 (p<0.001). The median %inhibition values by severity of COVID-19 symptoms were 79.9% (interquartile range (IQR) 49.7-91.8%); 89.0% (IQR 71.2-92.4%); and 86.6% (IQR 69.5-92.8%), for mild, moderate and severe/critical symptoms respectively. The median level of sVNT %inhibition of severe was significantly higher than the mild group (p = 0.05). Conclusion The sVNT is a practical and robust serological test for SARS-CoV-2 infection and does not require specialized biosafety containment. It can be used clinically to aid diagnosis in both early and late infection especially in cases when the real-time RT-PCR results in weakly negative or weakly positive, and to determine the protective immune response from SARS-CoV-2 infection in patients.